The reality of the myth: a structural-hermeneutical analysis - Baluta, Galyna (Actual Problems of Mind, 2017)
A myth can be regarded as a phenomenological structure with specific rules. The myth shows the phenomenon of "language aberration" and logical inversion: it refers not to a real prototype, but to a conditional representer, myth is based on modified logic or "logic of paradox".